Study on characteristics of aromatic lattice fringes in different rank coals - Guofei ZHAO; Xiaomin LIANG (Meikuang Anquan)
A systematic understanding of the characteristics and evolution of aromatic lattice fringes during coalification is beneficial to the safe mining and high-value utilization of coal resources. To elucidate the evolution of microcrystalline structures during coalification, we employed Digital Micrograph and ImageJ softwares for noise reduction, binarization, and skeletonization of the original high-resolution transmission electron microscopy (HRTEM) images. Subsequently, ArcGIS software was utilized to extract the aromatic lattice fringes from these images. We conducted a quantitative analysis of the morphology, length, angle, and stacking characteristics of aromatic lattice fringes in low-rank, mid-rank, and high-rank coals. The results show that the edges of aromatic lattice stripes in different rank coals are curved and characterized by short-range order and long-range disorder. With the increase of coal rank, the number of aromatic lattice fringes within the coal structure diminishes, while the orderliness and compactness of these fringes augment. Among the three coal samples analyzed, short fringes are most prevalent, long fringes are least abundant, and the quantity of aromatic lattice fringes exhibits a decreasing trend as fringe length increases. The specific gravity of polycyclic aromatic hydrocarbon sheets composed of 1-3 aromatic rings with carbon atoms less than 13 is the largest. The number of aromatic lattice fringes decreases with their length, the specific gravity of long fringes is positively correlated with the coal rank, the specific gravity of short fringes is negatively correlated with the coal rank, and the average length of aromatic lattice fringes increases with the coal rank. The orientation is the highest in high-rank coal, and the aliphatic hydrocarbon structure in middle-rank coal may cause the orientation to be less than that in low-rank coal. The overall order degree of aromatic lattice fringes increases with the coal rank. The number of aromatic lattice fringes stacks decreases with the increase of the number of stacking layers, and the number of fringes stacks increases with the coal rank. The removal of small molecular compounds and the change of aromatic ring condensation result in a constant change of microcrystalline structure from low to high rank coals.